Economical analyses of a rotavirus outbreak in a swine farm - Girotto, Ademir F.; Sobestiansky, Jurij; Mores, Nelson; Marques, José L. L.; Wentz, Ingon (Pesquisa Agropecuaria Brasileira, 2014)
The losses of a rotavirus outbreak, in Xanxerê SC, Brazil, in May 1987, after the repopulation of a crossbred sow production unit (220 sows) was economically analysed. The losses of animals due to rotavirus at the farrowing unit was 17,87% of the total piglets bom alive. At the nursey, the mortality was 1.67% of the total weaned pigs. Each dead animal in the farrowing unit or nursery due to outbreak represents the loss of a potential adult breeding animal, which is a waste of a net income loss of US$ 43.83. US$ 0.72 were spent with drugs tor the outbreak control of each animal bom alive in the period. The effective expenses due to outbreak (US$ 670.18) added to what was expected to be earned in the case that the dead animals were finished and sold as breeding pigs, were equivalent to 43.35 animals of about 103 kg of live weight.